Atlas of 3d echocardiography - Gill, Edward A. (Elsevier/Saunders, 2013)
Helps to identify complex geometrical distortions of cardiac anatomy and make more informed decisions regarding diagnosis and treatment. This title presents the authoritative, case-based, expert guidance you need to enhance your utilization and interpretation of this dimensional diagnostic tool.